Investigation of the homoiochlorophyllous desiccationtolerant dicot Haberlea rhodopensis Friv. during dessication and rehydration - Péli, Evelin Ramóna (Acta Biologica Szegediensis, 2005)
In this study the recovery of the photosynthetic activity during rehydration following dry stage was examined in the case of a homoiochlorophyllous desiccation-tolerant (HDT) plant, Haberlea rhodopensis. Although the majority of the DT plants are homoiochlorophyllous, we still do not have enough information about the HDT ones, especially information on flower DT plants are needed. Net CO2 assimilation (Pn) in Haberlea rhodopensis was characterized using data from measurements of CO2 gas exchange, the kinetics of chlorophyll fluorescence (variable Chl fluorescence ratio, Fv/Fm) in various hydration conditions. The pigment accumulation, thylakoid function and photosynthetic CO2 assimilation were fully recovered after rehydration. Long-term experiments would be needed to make a confident forecast of the responses of desiccation tolerant plants to the global environmental changes.